The Interplay Between Innate-Like B Cells and Other Cell Types in Autoimmunity - Tsay, Gregory J.; Zouali, Moncef (Frontiers in Immunology, 2018)
Studies performed in animal models and in humans indicate that the innate arm of the immune system provides an essential role in the initial protection against potential insults and in maintaining tolerance to self-antigens. In the B cell compartment, several subsets engage in both adaptive and innate functions. Whereas B cell subsets are recognized to play important roles in autoimmune diseases, understanding the intricacies of their effector functions remains challenging. In addition to B-1a cells and marginal zone B cells, the B cell compartment comprises other B cells with innate-like functions, including innate response activator B cells, T-bet positive B cells, natural killer-like B Cells, IL-17 producing B cells, and human self-reactive VH4-34–expressing B cells. Herein, we summarize the functions of recently described B cell populations that can exert innate-like roles in both animal models and humans. We also highlight the importance of the cross-talk between innate-like B cells and other adaptive and innate branches of the immune system in a variety of autoimmune and inflammatory diseases. In as much as innate immunity seems to be important in resolving inflammation, it is possible that targeting certain innate-like B cell subsets could represent a novel therapeutic approach for inducing resolution of inflammation of autoimmune and inflammatory responses.